Comparison and analysis of the efficacy and safety of minimally invasive surgery and craniotomy in the treatment of hypertensive intracerebral hemorrhage - Zhang, Jixin (Pak J Med Sci, 2018)
OBJECTIVE: This study was aimed to compare and analyze the effects and safety of minimally invasive and craniotomy in the treatment of hypertensive intracerebral hemorrhage. METHODS: A total of 130 patients with hypertensive intracerebral hemorrhage were recruited. The patients were randomly divided into two groups (research and control group). Research group was treated with endoscopic minimally invasive surgery, while control group was treated with craniotomy and hematoma clearance. The basic situation, clinical effects, prognosis, nerve function and inflammatory factors of the two groups were compared while the condition of postoperative complications was also observed. RESULTS: The operative time of patients in research group showed statistically significant (P<0.05) difference when compared with control group. Hematoma clearance rate and intraoperative blood loss of research group was significantly better than control group. There was no significant difference (P>0.05) between the two groups in preoperative hemorrhage and edema around the hematoma, however hemorrhage and edema around the hematoma after four weeks of surgery in the research group was significantly (P<0.05) lower than control group. After four weeks of treatment, the BI and SSS score, SP and IL-2 level of the research group were significantly higher than control group (P<0.05), while MRS score, IL-6, hs-CRP, TNF-α and SF was significantly lower than control group (P<0.05). CONCLUSION: Compared with craniotomy, minimally invasive surgery is more effective in the treatment of hypertensive intracerebral hemorrhage, as well as it is more conducive to restore neurological function, improve prognosis and reduce serum inflammatory factor levels.